REVERSIBLE OBSTRUCTIVE SLEEP APNEA AND RIGHT HEART FAILURE DUE TO MASSIVE TONSILLAR HYPERTROPHY - Atiq, Mehnaz; Masood, Fatima; Ikram, Mubashir; Haqqee, Raana (Journal of Ayub Medical College Abbottabad, 2004)
Obstructive sleep apnea is a relatively common but under diagnosed clinical entity in children. Adenotonsillar hypertrophy is the most common cause for upper airway obstruction in pediatric patients. If the obstruction to upper airways is not relieved, then the child can develop obstructive sleep apnea and its consequences. Treatment is simply to remove the obstruction thereby restoring patency of upper airways Key Words: Obstructive sleep apnea, pulmonary hypertension, adenoid hypertrophy, tonsil hypertrophy.